Coronarin K and L: Two Novel Labdane Diterpenes From Roscoea purpurea: An Ayurvedic Crude Drug - Venugopal Singamaneni (Frontiers Media S.A., 2021)
The main objective of cancer treatment with chemotherapy is to kill the cancerous cells without affecting the healthy normal cells. In the present study, bioactivity-guided purification of the n-chloroform soluble fraction from the methanol extract of Roscoea purpurea resulted in the identification of two new labdane diterpenes: coronarin K (1) and coronarin L (2), along with eight known compounds, coronarin A (3), bisdemethoxycurcumin (4), kaempferol 3-O-methyl ether (5), kaempferol (6), fenozan acid (7), 3-(3-methoxy,4-hydroxyphenyl)-2-propenoic acid ferulic acid (8), caffeic acid (9), and gallic acid (10). The structural identification of new compounds (1 and 2) were determined by detailed analysis of 1D (1H and 13C) and 2D NMR (COSY, HSQC, and HMBC) spectroscopic data. The relative configurations of 1 and 2 were determined with the help of NOESY correlations and comparison of optical rotations with known labdane diterpenes, with established stereochemistry, while structure of known compounds was established by direct comparison of their NMR data with those reported in the literature. This is the first report of isolation of this labdane diterpenes and phenolic classes of secondary metabolites in R. purpurea. In the preliminary screening, the methanol extract and its fractions were tested for the cytotoxic activity against a panel of four cancer cell lines (A549, HCT-116, Bxpc-3, and MCF-7); extract and its chloroform fraction were found to be active against the lung cancer cell line, A-549, with IC50 value <25 μg/ml. Owing to the notable cytotoxic activity of the chloroform fraction, the compounds (1–5) were screened for their cytotoxicity against all the cell lines by MTT assay. Coronarin K, 1 showed significant cytotoxic potential against lung cancer cell lines (A-549), with IC50 value of 13.49 μM, while other compounds did not show activity below 22 μM.